RIME proteomics of estrogen and progesterone receptors in breast cancer - D’Santos, Clive (Data Brief, 2015)
Nuclear receptors play an important role in transcriptional regulation of diverse cellular processes and is also relevant in diseases such as cancer. In breast cancer, the nuclear receptors – estrogen receptor (ER) and progesterone receptor (PR) are classical markers of the disease and are used to classify breast cancer subtypes. Using a recently developed affinity purification MS technique (RIME) [1], we investigate the protein interactors of ER and PR in breast cancer cell lines upon stimulation by the ligands – estrogen and progesterone. The data is deposited at proteomeXchange (PXD002104) and is part of a publication [2] that explains the link between the two nuclear receptors and potential consequences of this in breast cancer. In this manuscript, we describe the methodology used and provide details on experimental procedures, analysis methods and analysis of raw data. The purpose of this article is to enable reproducibility of the data and provide technical recommendations on performing RIME in hormonal contexts.